2023
DOI: 10.1177/00037028231200511
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Parameters During Nanoparticle-Enhanced Laser-Induced Breakdown Spectroscopy (NELIBS) in the Presence of Nanoparticle–Protein Conjugates

Marcella Dell’Aglio,
Antonia Mallardi,
Rosalba Gaudiuso
et al.

Abstract: Nanoparticle-enhanced laser-induced breakdown spectroscopy (NELIBS) is an optical emission technique based on the laser-induced plasma (LIP) on a sample after the deposition of plasmonic nanoparticles (NPs) on its surface. The employment of the NPs allows an enhancement of the signal with respect to the one obtained with the conventional laser-induced breakdown spectroscopy (LIBS) enabling an extremely high sensitivity and very low limits of detection compared with the LIBS performance. Recently, NELIBS was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Further, the EF of K I 769.90 nm showed a maximum of 2.94 at 2.5 μL. The EF factors obtained in this work are similar to the recent results reported by Dell'Aglio et al , 39 who showed that the net NELIBS enhancement factor of titanium (Ti) targets containing a mixture of human serum albumin (HSA) and Au NPs was also about 3. This shows the advantage and application potential of NELIBS in element detection using minor sample volumes.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Further, the EF of K I 769.90 nm showed a maximum of 2.94 at 2.5 μL. The EF factors obtained in this work are similar to the recent results reported by Dell'Aglio et al , 39 who showed that the net NELIBS enhancement factor of titanium (Ti) targets containing a mixture of human serum albumin (HSA) and Au NPs was also about 3. This shows the advantage and application potential of NELIBS in element detection using minor sample volumes.…”
Section: Resultssupporting
confidence: 90%
“…12,40,51,52 Meanwhile, the results also indicate that the plasma parameters are not strongly affected by the interaction between the Ag NPs and proteins, such as the protein corona, which has also been demonstrated in a study on protein corona and Au NPs. 39 Moreover, according to the simulation of the Cu I emission line by Soumyashree and Kumar, 53 when the electron density is in the order of 1 ×10 17 cm −3 and the electron temperature is within the range of 1-1.4 × 10 4 K, the EF would decrease with an increase in electron temperature, which also explains the downward trend of EF with decreasing Ag NPs concentration (with slightly increased T e ) in Fig. 8.…”
Section: Effect Of Ag Nps Concentrationmentioning
confidence: 81%
See 2 more Smart Citations